2018
DOI: 10.37358/rc.17.12.6021
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Botulinum Neurotoxin Treatment in a Multitude of Medical Conditions

Abstract: Botulinum neurotoxins (BoNTs) are responsible for botulism in humans and vertebrates, being one of the six most catastrophic potential bioterrorism agents. This are ~150 kDa proteins, assembled as a ~50 kDa light chain (LC) and a ~100 kDa heavy chain (HC). The LC acts like a zinc metalloproteinase that cleaves three proteins in neurons, members of the SNARE (Soluble N-ethylmaleimide sensitive fusion attachment protein receptors) family: VAMP (vesicle-associated membrane protein) / synaptobrevin, SNAP-25 (synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Intravenous administered Nefopam determines a strong inhibition of the nociceptive flexion reflex in humans [21]. Studies has shown that it has opioid-sparing effects (it reduces de opioid consumption after cholecystectomy [22], cardiac surgery [11], upper and lower abdominal surgery [23,24], hysterectomy [25], palliative interventions [26,27], breast cancer surgery [28], nasal surgery, orthopedic interventions [29,30], by 30-40% [2] and that 20 mg of Nefopam is equipotent with almost 6-12 mg Morphine and 50 mg of Meperidine [31] having the same analgesic potency as nonsteroidal anti-inflammatory drugs.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Intravenous administered Nefopam determines a strong inhibition of the nociceptive flexion reflex in humans [21]. Studies has shown that it has opioid-sparing effects (it reduces de opioid consumption after cholecystectomy [22], cardiac surgery [11], upper and lower abdominal surgery [23,24], hysterectomy [25], palliative interventions [26,27], breast cancer surgery [28], nasal surgery, orthopedic interventions [29,30], by 30-40% [2] and that 20 mg of Nefopam is equipotent with almost 6-12 mg Morphine and 50 mg of Meperidine [31] having the same analgesic potency as nonsteroidal anti-inflammatory drugs.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Stent coating presents many improvements, such as the decrease of biofilm onset, inflammation and also in friction, and consequently lowering the risk of infections and an easier stent passage over a guidewire, too. Specific coatings may also be employed for drug eluting purpose [14]. Numerous strategies have been developed and tested, largely based upon the application of anti-adhesive and antimicrobial compounds.…”
Section: Stent Coatingmentioning
confidence: 99%
“…Most of these stents are placed for 2-3 weeks, but there are situations that require a longer period up to years. Usually patients with short-term stent placement present pain and discomfort during activity and urination [13], requiring analgesic medication or other types of procedures [14].…”
mentioning
confidence: 99%
“…The main reason for increased serum levels of CK is a skeletal muscle lesion and it is possible to find elevation of CK after intramuscular injections and intense exercise [1,3], but usually significant increases of CK are found in major muscular or neuromuscular pathology as polymyositis, dermatomyositis, rhabdomyolysis, muscular dystrophies, drug-induced myopathies, seizures, malignant hyperthermia, malignant neuroleptic syndrome [7][8][9][10][11] in association with the increase of other enzymes as lactate dehydrogenase (LDH), aldolase or muscular components as myoglobin, being very problematic for patients with impaired renal function, especially if they need to go under surgery [12][13][14]. High levels are often encountered in case of bone fractures which needs extensive muscle and periosteum trauma and in aggressive tumors that have invaded the muscle tissue [15][16][17][18]. CK levels are useful not only for the diagnosis but also for monitoring these conditions.…”
mentioning
confidence: 99%
“…It is important to emphasize that persistent increases in CK in athletes after rest, even without symptoms, could indicate a muscular disease in early preclinical phase or muscular impairment function [3,19]. Amongst drug-induced muscular reactions, statin associated muscular symptoms (SAMS) are very frequent (7-29% of all treated patients) and a major cause of statin therapy non-adherence or discontinuation (65-75%) [8]. Due to the worldwide use of statins for prevention of cardiovascular events, the number of patients affected by SAMS is very high and continues to grow as statin therapy is extending, raising important issues in then subgroup of patients having chronic renal failure [20,21] but the majority of patients will have normal or slightly elevated CK levels [10,22].…”
mentioning
confidence: 99%